Recuento plaquetario elevado como factor de riesgo para cáncer de colon metastásico en pacientes del Instituto Regional de Enfermedades Neoplásicas - Vizconde Rodríguez, Ana Paula (2022)
Worldwide, colorectal cancer is the third most common cancer in both sexes, but in developed countries it is the second. It is possible that interactions between platelets and tumor cells influence the process of tumor metastasis. Antiaggregants and anticoagulants have a powerful inhibitory effect on the interactions between platelets and tumor cells, as well as on spontaneous or experimental metastases. In this sense, the study of the role of cytokines and treatment with antiaggregants and anticoagulants could become clinically useful, especially in patients with other poor prognostic factors, especially the advanced clinical stage.